Hera: Decifradores dos mitos esquecidos Um grupo de poetas e uma revista de poesia no cenário da literatura baiana - Lima, Jecilma Alves (2007)
The dissertation entitled Hera: "Decifradores dos mitos esquecidos" Upoetas e uma revista de poesia no cenário da literature baiana performs an analysis of the training and assistance of the magazine HERA and the group homonym, which appears in Feira de Santana, Bahia, in 1973 with the intent to deploy in a city accused of aversion to the cultural and artistic issues, a project that would not only disseminate new literary values, but also train and extend a public reader of the new poetry that circulating the country. In this regard, the study makes a resumption of contributions and problems faced by literary magazines in Brazilian modernism, and in the Bahia, and its developments through the century to present the cultural context in which emerge the magazine, analyzing your itinerary over thirty - three years, the numbers between 1 and 20. Then are considered most representative of the peculiarities of each generation and poets, such as poems published fit in a row aesthetic and ideological, talking things through formal and thematic axes. Finally are considered trademarks cultural city in the texts published in the HERA.